1994
DOI: 10.1103/physreve.49.2684
|View full text |Cite
|
Sign up to set email alerts
|

Inverse avalanches in the Abelian sandpile model

Abstract: We define and study the inverse of particle addition process in the Abelian sandpile model. We show how to obtain the unique recurrent configuration corresponding to a single particle deletion by a sequence of operations called inverse avalanches. We study the probability distribution of sl, the number of "untopplings" in the first inverse avalanche. For a square lattice, we determine Prob (sl ) [7]. If from a spanning tree we delete a bond at random, the probability distribution of the number of sites disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 13 publications
3
45
0
Order By: Relevance
“…In the Potts model formulation these will be the Oðq 2 Þ terms in the partition function in Eq. (39). It is sometimes convenient to work in the ensemble in which all waves are given equal weight in determining avalanche statistics.…”
Section: Waves Of Topplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Potts model formulation these will be the Oðq 2 Þ terms in the partition function in Eq. (39). It is sometimes convenient to work in the ensemble in which all waves are given equal weight in determining avalanche statistics.…”
Section: Waves Of Topplingmentioning
confidence: 99%
“…Dhar and Manna showed that the distribution of the number of sites toppled in the last wave can be related to number of sites disconnected if a bond is deleted at random from a random spanning tree [39]. The latter is expressible in terms of the chemical exponent for spanning trees.…”
Section: Waves Of Topplingmentioning
confidence: 99%
“…(25,27,30). Using the Kirchhoff's theorem one can determine, in principle, all of the correlations between different branches of spanning trees.…”
Section: Correlation Functions and The Continuous Limitmentioning
confidence: 99%
“…in [68] as hole addition then followed by hole avalanches in order to reach a stable configuration. Also inverse avalanches has been introduced before, in [69], to get back to the recurrent configuration after the deletion of a particle in a configuration of the ASM.…”
Section: Theoremmentioning
confidence: 99%